Is green and sustainable technological innovation a potential driver of environmental performance? an empirical investigation across the ASEAN region - Rehman, Shazia; Holý, Ondřej (Frontiers in Environmental Science, 2022)
Environmental degradation is a significant concern that jeopardizes global sustainable production and consumption. In this instance, ASEAN (Association of South-East Asian Nations) has contributed to a considerable amount of carbon dioxide (CO2) emissions throughout the modernization phase. However, there is a paucity of information within this region on the non-linear impact of transitions in green and sustainable technological innovation on CO2 emissions. In response, the present work endeavors to bridge the existing research gap by examining the asymmetrical and periodic interactions between green and sustainable technological innovation and CO2 emissions by employing cross-sectional time series data of 7-ASEAN economies over the period 1990 to 2017. The co-integrating connections between the specified parameters were established using the Wester-Lund cointegration technique. Further, the Cross-Sectionally Augmented Autoregressive Distributed Lag estimator revealed that negative disruptions in green and sustainable technological innovation lead to CO2 emissions during downturns. Secondarily, the findings confirmed positive surges in green and sustainable technological innovation minimize CO2 emissions during times of economic expansion. Also, as compared to foreign direct investment, current statistics indicate that renewable energy utilization seems to have a substantial impact on reducing carbon emissions. Besides, the robustness analysis corroborated the uniformity and validity of the given outcomes. Consequently, the outcomes divulged a counter-cyclical interaction between green and sustainable technological innovation and CO2 emissions.